DDE and PCB serum concentration in maternal blood and their adult female offspring - Hsu, Wei-Wen; Osuch, Janet Rose; Todem, David; Taffe, Bonita; O’Keefe, Michael; Adera, Selamawit; Karmaus, Wilfried (My University, 2014)
Background: Dichlorodiphenyl dichloroethylene (DDE) and polychlorinated biphenyls (PCBs) can be passed from mother to offspring through placental transfer or breast feeding. Unknown is whether maternal levels can predict concentrations in adult offspring. Objectives: To test the association between maternal blood levels of DDE and PCBs and adult female offspring levels of these compounds using data from the Michigan Fisheaters’Cohort. Methods: DDE and PCB concentrations were determined in 132 adult daughters from 84 mothers. Prenatal exposures were estimated based on maternal DDE and PCB serum levels measured between 1973 and 1991. Levels in adult daughters were regressed on maternal and estimated prenatal exposure levels, adjusting for potential confounders using linear mixed models. Confounders included daughter’s age, birth order, birth weight, number of pregnancies, the length of time the daughter was breast-fed, the length of time the daughter breast-fed her own children, last year fish-eating status, body mass index, and lipid weight. Results: The median age of the participants was 40.4 years (range 18.4 to 65.4, 5–95 percentiles 22.5-54.6%, respectively). Controlling for confounders and intra-familial associations, DDE and PCB concentrations in adult daughters were significantly positively associated with estimated prenatal levels and with maternal concentrations. The proportion of variance in the adult daughters’ organochlorine concentrations explained by the maternal exposure levels is approximately 23% for DDE and 43% for PCBs. The equivalent of a median of 3.67 μg/L prenatal DDE and a median of 2.56 μg/L PCBs were 15.64 and 10.49 years of fish consumption, respectively. When controlling for effects of the shared environment (e.g., fish diet) by using a subsample of paternal levels measured during the same time frames (n=53 and n=37), we determined that the direct maternal transfer remains important. Conclusions: Estimated intrauterine DDE and PCB levels predicted concentrations in adult female offspring 40 years later. Interpretation of adverse health effects from intrauterine exposures of persistent pollutants may need to consider the sustained impact of maternal DDE and PCB levels found in their offspring.
Keywords: Intra-uterine exposure; Dichlorodiphenyl dichloroethylene; Polychlorinated biphenyls; Sport-caught fish consumption; Female offspring